2017
DOI: 10.1007/s00204-017-1981-2
|View full text |Cite|
|
Sign up to set email alerts
|

Role of the aryl hydrocarbon receptor in carcinogenesis and potential as an anti-cancer drug target

Abstract: The aryl hydrocarbon receptor (AhR) was initially identified as the receptor that binds and mediates the toxic effects induced by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and structurally related halogenated aromatics. Other toxic compounds including some polynuclear aromatic hydrocarbons act through the AhR; however, during the last 25 years, it has become apparent that the AhR plays an essential role in maintaining cellular homeostasis. Moreover, the scope of ligands that bind the AhR includes endogenous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 170 publications
2
94
0
Order By: Relevance
“…TCDD promotes cell proliferation such as breast cancer stem cells (40) and hepatic stem cells (29) via AHR-dependent pathway, indicating that AHR may be a potential target for cancer chemotherapy (41). AHR is involved in various aspects of cardiovascular homeostasis and diseases, including cardiomyocyte differentiation in embryonic development (42), angiotensin II release from endothelial cells in hypertension (43), and vascular remodeling in placenta (44).…”
Section: Discussionmentioning
confidence: 99%
“…TCDD promotes cell proliferation such as breast cancer stem cells (40) and hepatic stem cells (29) via AHR-dependent pathway, indicating that AHR may be a potential target for cancer chemotherapy (41). AHR is involved in various aspects of cardiovascular homeostasis and diseases, including cardiomyocyte differentiation in embryonic development (42), angiotensin II release from endothelial cells in hypertension (43), and vascular remodeling in placenta (44).…”
Section: Discussionmentioning
confidence: 99%
“…The aryl hydrocarbon receptor (AhR) belongs to the family of basic helix‐loop‐helix transcription factors and is known to mediate the effects of polycyclic and polyhalogenated aromatic hydrocarbon ligands, including environmental toxins such as benzo[ a ]pyrene ( 1 ) and 2,3,7,8‐tetrachlorodibenzo‐ p ‐dioxin ( 2 ) . Multiple other ligands, including bilirubin, prostaglandins, tryptophan, and even plant‐derived ligands such as resveratrol and flavones also exist .…”
Section: Introductionmentioning
confidence: 99%
“…(2). [5][6][7][8][9] Multiple other ligands, including bilirubin, prostaglandins, tryptophan, and even plant-derived ligands such as resveratrol and flavones also exist. [10,11] Ongoing analysiso fA hR functioni sr evealing the increased complexity of this pathway, with evidence that the AhR has the ability to modulate gene transcription and other cellular events without ligand activation.…”
Section: Introductionmentioning
confidence: 99%
“…Benzo[α]pyrene (BaP) is one of the major compounds of the PAH family that can be found at high levels in cigarette smoke (Schneider, Roller, Kalberlah, & Schuhmacher‐Wolz, ). Studies have shown that BaP acts as an exogenous ligand for aryl hydrocarbon receptor (AhR) (Kolluri, Jin, & Safe, ). AhR is a transcription factor of Per‐ARNT‐Sim‐basic‐helix‐loop‐helix (PAS‐bHLH) family proteins.…”
Section: Introductionmentioning
confidence: 99%
“…exogenous ligand for aryl hydrocarbon receptor (AhR) (Kolluri, Jin, & Safe, 2017). AhR is a transcription factor of Per-ARNT-Sim-basichelix-loop-helix (PAS-bHLH) family proteins.…”
mentioning
confidence: 99%